The enactment of the Malaysian common European framework of reference (CEFR): National master trainer’s reflection - Aziz, Abdul Hakim Ali Abdul; Rashid, Radzuwan Ab; Zainudin, Wan Zhafirah Wan (Universitas Pendidikan Indonesia, 2018)
As Malaysia sets out to realise their plan of the English Language Education Reform, the adaptation and implementation of Common European Framework of Reference (CEFR) is an obvious choice; however, creating a high-calibre teaching workforce to carry it out poses a significant challenge. This critical reflection article elucidates the implementation of CEFR in Malaysian Pre-, Primary and Secondary schools from the perspective of a National Master Trainer (NMT) who attended multiple courses by Cambridge English Super Trainers (CEST) before going on to train English language teachers using the Cascade Training Model. Based on the trainer’s experience, this article discusses the progress of the training, starting from CEST as the first tier, NMT as the second tier, and District Trainer (DT) as the third tier, until it reaches the teachers who will apply their knowledge and skills in the classroom. We conclude that despite the long and careful planning in terms of teacher training for the CEFR implementation, there are various aspects that need improvements, to better guarantee success in producing an English language programme along with international standards, as the plan dictates.